2010
DOI: 10.1186/1471-2369-11-30
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute kidney injury following orthotopic liver transplantation: the impact of changes in renal function while patients await transplantation

Abstract: BackgroundAcute kidney injury (AKI) occurs commonly in the setting of orthotopic liver transplantation (OLT). To date, the correlation between AKI post-OLT and pre-operative changes in renal function has not been rigorously examined.MethodsTo determine the impact of pre-OLT changes in renal function on AKI post-OLT, as well as to identify risk factors for AKI, we analyzed the prospectively maintained NIDDK Liver Transplantation Database, which includes patients who received their first OLT between April 15, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 36 publications
2
23
1
Order By: Relevance
“…These observations confirm the findings of previous studies (6,8,36). In agreement with our study, higher BMI has been linked to renal failure (37,38) and has been shown to be an independent risk factor for developing AKI in ICU patients in general (39), as well as in specific subgroups such as septic (8) or liver transplant patients (40). It is no surprise that ACEI/ ARB use was an independent predictor of AKI.…”
Section: Discussionsupporting
confidence: 93%
“…These observations confirm the findings of previous studies (6,8,36). In agreement with our study, higher BMI has been linked to renal failure (37,38) and has been shown to be an independent risk factor for developing AKI in ICU patients in general (39), as well as in specific subgroups such as septic (8) or liver transplant patients (40). It is no surprise that ACEI/ ARB use was an independent predictor of AKI.…”
Section: Discussionsupporting
confidence: 93%
“…The 15,17 , preoperative decreased renal function 7,17 , hemocomponents transfusion 1,5,18 , postreperfusion syndrome 5,19 and surgical technique 1,2 have been highlighted in the most current literature. Some preoperative co-morbidity such as hypertension, obesity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Some preoperative co-morbidity such as hypertension, obesity (i.e. : increased BMI) and diabetes mellitus have also been related to outcomes after OLT when the renal dysfunction is explored in the settings of OLT 4,7,20 . Using this same cohort, we previous presented that patient/liver disease severity (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies was found discrepancies (13% to 94%) in incidence, and this occurred due to lack of consensus on the definition of ARF after liver transplantation 35 . The preoperative AKI is considered a risk factor for the development of ARF in transplants 12 . The preoperative renal function, assessed by serum creatinine, is part of the MELD score is a stratification of patients on the waiting list for liver transplantation 14,30 .…”
Section: Discussionmentioning
confidence: 99%